2019
DOI: 10.1002/geo2.76
|View full text |Cite
|
Sign up to set email alerts
|

Mapping microbial stories: Creative microbial aesthetic and cross‐disciplinary intervention in understanding nurses’ infection prevention practices

Abstract: Consistent implementation of hand‐washing within the hospital environment remains a challenge in infection prevention (IP) procedures. IP is one of a number of measures to tackle antimicrobial resistance (AMR). A cross‐disciplinary team was assembled to experiment with different ways of visualising the microbial. The paper details a comparative experimental design where nurses (n = 2) performed a series of routine care procedures in a mock‐ward setting where traces of coloured ultra‐violet glow‐powders had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Deprived of reliable supplies of personal protective equipment, they have repeatedly put themselves at risk while helping others to mitigate risk, often with the knowledge that they will be seenlike MSF doctors fighting Ebola (Pallister-Wilkins, 2016)as risky neighbors and family members back in their home communities. All this urgent care work has underlined anew both the vulnerability and indispensability of health care workers globally, and thus the salience of arguments about their central but often ignored role in the geography of health, including as what Emma Roe and colleagues call "microbial citizens" who take care of the micro-geographies of infection (Connell & Walton-Roberts, 2016;Enticott & Ward, 2020;Roe et al, 2019). As feminist geographers have underlined, such work is also often gendered as "women's work," and, as a sexist result, reproduces care geographies that are as globally devalued as they are personally and intimately taken-for-granted (Bartos, 2019;Lopez, 2019).…”
Section: Geographies Of Carementioning
confidence: 99%
“…Deprived of reliable supplies of personal protective equipment, they have repeatedly put themselves at risk while helping others to mitigate risk, often with the knowledge that they will be seenlike MSF doctors fighting Ebola (Pallister-Wilkins, 2016)as risky neighbors and family members back in their home communities. All this urgent care work has underlined anew both the vulnerability and indispensability of health care workers globally, and thus the salience of arguments about their central but often ignored role in the geography of health, including as what Emma Roe and colleagues call "microbial citizens" who take care of the micro-geographies of infection (Connell & Walton-Roberts, 2016;Enticott & Ward, 2020;Roe et al, 2019). As feminist geographers have underlined, such work is also often gendered as "women's work," and, as a sexist result, reproduces care geographies that are as globally devalued as they are personally and intimately taken-for-granted (Bartos, 2019;Lopez, 2019).…”
Section: Geographies Of Carementioning
confidence: 99%
“…The discount in contamination prices, exemplified through the tremendous decreases in Healthcare-Associated Infections (HAI) and Antibiotic-Resistant Infections (ARI), aligns with findings from previous research. Roe et al (2019b) [16] and Samreen et…”
Section: Discussionmentioning
confidence: 96%
“…While previous research has demonstrated the advantageous impact of incorporating microbiological views on infection control measures and patient results, there may be constrained exploration into the unique methodologies or models that correctly bridge the space between medical studies and policy formulation. This examines objectives to cope with this gap by way of introducing a unique method that systematically evaluates the pathways through which microbiological records inform and shape healthcare guidelines (Roe et al, 2019a) [15] . The novelty lies in the complete analysis of the interpretation system, delineating the steps, demanding situations, and facilitators involved in integrating microbiological evidence into coverage frameworks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholarly interest in the unfolding of social worlds through emotions, affects, practices and multisensual forces has found synergies with artistic approaches to microbial research that illustrate other ways of knowing and communicating the micro-scale (see Evans and Lorimer, 2021;Macduff et al, 2017). An important contribution from Roe et al (2019) foregrounds aesthetics and imaginaries in illustrating microbial interactions with humans in the act of infection. Such work advocates for non-anthropogenic modes of researching with microbial worlds and attending to the material and imaginative, subtle and dynamic, forces they engineer (see Hinchliffe et al, 2005).…”
Section: Charlotte Veal Paul Hurley Emma Roe and Sandra Wilksmentioning
confidence: 99%
“…Paul Hurley (PH): So, we had a filmmaker on board from the outset, Joseph Turp. Joe had worked with the research team on Mapping Microbes in 2016; a project that developed creative visualisations of surface transmission and hand hygiene in a mockhospital ward (Roe et al, 2019). Joe was involved in the developmental phase of Routes to Safety and this helped coordinate our thinking on outputs.…”
Section: Context For the Filmmentioning
confidence: 99%